Chemical fertilizer reduction combined with bio-organic fertilizers increases cauliflower yield via regulation of soil biochemical properties and bacterial communities in Northwest China - Xiao, Xuemei; Li, Ju; Lyu, Jian; Feng, Zhi; Zhang, Guobin; Yang, Haixing; Gao, Chengfei; Jin, Li; Yu, Jihua (Frontiers in Microbiology, 2022)
The continuous application of chemical fertilizers in vegetable cropping has led to deterioration of the soil environment and reduced yield and quality. The objective of this study was to evaluate the effect of combining chemical and bio-organic fertilizers on cauliflower yield, soil biochemical properties, and the bacterial community. Six treatments were established: no fertilizer (CK, control), chemical fertilizers (CF, conventional dosage for this region), balanced fertilization (BF, 30% reduction of chemical fertilizers), and balanced fertilization plus 3,000, 6,000, or 12,000 kg·ha-1 bio-organic fertilizer (Lvneng Ruiqi Biotechnology Co., Ltd, Gansu, China) (BF+OF1, BF+OF2, BF+OF3, respectively). A two-season field experiment with cauliflower was conducted under the different fertilizer treatments in irrigation districts along the Yellow River, Northwest China. The results indicate that the yield, soil organic matter, total potassium content, and enzyme activity under the bio-organic treatments were generally higher than those under the CF treatment. Compared with the CF treatment, the BF treatment increased soil organic matter content, enzyme activity and soil bacterial relative abundance. Moreover, the bacterial alpha-diversity were higher than those of conventional fertilization. The predominant phyla, including Proteobacteria, Actinobacteria, Gemmatimonadetes, and Chloroflexi, were the main contributors to the microbiome shift, as demonstrated by their remarkable enrichment in the soil under BF+OF2 and BF+OF3 treatments. Furthermore, Pearson correlation analyses show significant correlations among the soil organic matter, available P and K, electrical conductivity, and relative abundance of potentially beneficial microbial groups, such as the genera Massilia, Bacillus, Lysobacter, and Nitrosospira. Overall, this study suggests that balanced fertilization and the application of bio-organic fertilizers are essential to ensure soil fertility and long-term sustainable green productivity.